Application of the Newmark Analysis Method in Stability Evaluation of Submarine Slope. (22nd July 2021) - Chu, Hongxian; Feng, Yongcai; Shi, Huijie; Hao, Liancheng; Gao, Yiqi; Chen, Yuhai
Abstract : The Newmark seismic time-history analysis method can take into account the effects of natural seismic peak ground acceleration (PGA), duration, and seismic frequency; seismic wave can be input into the method for simulation. This study calculates the dynamic response of the typical seabed slope of Caofeidian in the event of a similar Tangshan earthquake, and the displacement value can be used to quantitatively reflect the influence of the earthquake on the slope of the site. The allowable displacement value of the top of buildings or submarine slope can be used as a marker of security and stability analysis, which can further provide important reference for similar slope stability evaluation and offshore engineering construction.